Interaksi Edukatif dalam Pendidikan Islam: Telaah atas Pemikiran Muhammad ‘Athiyah Al-Abrosyi (THUFULA, 2014)
The relationship of teachers and students is described as partnersthat form symbiotic mutualism. The harmony in educational interactionsignificantly impacts on the success of the learning process in the classroom.Teachers as educators and teachers must be able to play in empoweringlearners to become learners who are not qualified only intellectually but havemoral quality (akhlakul mahmudah). The educational interaction that upholdsmoral principles and morals must take precedence. In view of ‘Athiyah al-Abrosyi educational interaction in the learning process should be based ethicalprinciples that should be owned by teachers and learners. In the educationalinteraction, the teacher has a central role. In addition to teaching, then it ismore important is the educator. The teacher described as a spiritual fatherfor students, in addition to providing knowledge, is educating morals. And forlearners in learning should have ethics, which in turns have an impact on thesuccess of the world and the hereafter.